Improved decision directed carrier phase estimation for nonlinearity mitigation in 16-QAM systems - Pakala, Lalitha; Schmauß, Bernhard (International Conference on Transparent Optical Networks (ICTON), 2014)
We propose and numerically investigate an improved decision directed (IDD) carrier phase estimation (CPE) to mitigate fiber nonlinearity in 16 quadrature amplitude modulation (QAM) coherent transmission systems. The proposed IDD-CPE algorithm is derived based on a two stage approach and compared with other CPE algorithms namely, the pre-decision directed (PDD) CPE and the decision directed (DD) phase locked loop (PLL). By exploiting the symbol position information in the I-Q plane and a euclidean distance measure, the proposed IDD-CPE algorithm outperforms the PDD-CPE and DD-PLL methods, exhibiting an optimal performance at signal launch power of 0 dBm and at optical signal to noise ratios (OSNRs) greater than 28dB, where no bit errors are detected.
lhft_intern.bib::Pakala2014b